Edukasi & Pelatihan Kader Kesehatan DI Desa Batok: Hands-Only Cardiopulmonary Resuscitation (CPR) & Pemberian Terapi Oksigen - Aruan, Maroloan; Saputra, Bima Adi; Pailak, Heman; Lusiana, Diana Intan Gabriella; Widodo, Putri Aprilia; Bramita, Anastasia Aprilia; Latuhihin, Trimeivi Dalmatia; Ananda, Glorya Natalie Dwi (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Batok Village faces challenges in emergency health services, especially related to respiratory arrest and cardiac arrest due to hypoxia. The low understanding of posyandu cadres on first aid techniques such as Hands-Only Cardiopulmonary Resuscitation (HO-CPR) and oxygen therapy is the main issue in thi Community Service (PkM) activity. The activity was carried out with a service-learning approach, involving lecturers and students of Universitas Pelita Harapan in training cadres from 12 posyandu. The method used was pre-experimental with a pre-test and post-test design to measure the effectiveness of the training. The evaluation results showed an increase in the average knowledge of participants from 62.46% to 77.3%, with a significant increase in the technical aspects of CPR. Although there was a decrease in some aspects, this activity succeeded in improving cadres’ competence in emergency management. This program is expected to strengthen community preparedness in dealing with cardiac arrest and hypoxia cases, and become a sustainable education model for village communities.